Pengaruh Ukuran Perusahaan, Leverage, Sales Growth Dan Investment Opportunity Set Terhadap Nilai Perusahaan - Agustina Khoeriyah (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
This study aims to determine the effect of firm size, leverage , sales growth, and investment opportunity set to the value of company. The sample in this study were 53 data from 18 mining companies listed on the Indonesia Stock Exchange in the 2015-2018 period that met the criteria. This type of research is quantitative and the sample used is purposive sampling. The analysis of the data used is the statistical analysis in the form of multiple linear regression. The results of this study indicate that firm size does not effect the firm value, leverage has a significant negative effect on firm value, sales growth and investment opportunity set has a significant positive effect on firm value.